Fundamentals of fluid mechanics - Schetz, Joseph A.; Fuhs, Allen E. (John Wiley & Sons, 1999)
Basic fluid dynamic theory and applications in a single, authoritative reference The growing capabilities of computational fluid dynamics and the development of laser velocimeters and other new instrumentation have made a thorough understanding of classic fluid theory and laws more critical today than ever before.